Mosque Debates as Space-related, Intercultural, and Religious Conflicts, - Schmitt, Thomas (Migration, Religion, and Germany, 2012)
The debate about a new mosque in Manhattan to be located near Ground Zero echoed around the world in 2010. Since the end of the 1980s, plans for new mosques have been highly contested in the western world. The main aim here is a comparison of different mosque conflicts, with a focus on German examples. “No mosque in our town!” is, with its variants, a common slogan of local neighbors and citizen action groups in Germany when a new mosque is to be built. So it is only a minor exaggeration to state: “No new mosque in Germany without a local conflict.” Also, since the late 1980s, inconspicuous mosques in Germany have been increasingly replaced by buildings that combine traditional elements of Islamic architecture (minarets, domes) with modern western and postmodern forms. This analysis differentiates at least three aspects of these conflicts: (1) spatial aspects, e.g., questions of town planning, but also the relevance of the built environment for personal and collective identity, (2) interethnic and intercultural aspects, e.g., the relation between the establishment and outsiders, and (3) interreligious aspects, e.g., the mutual conceptualizations of Islam and Christianity or relations between Islamic organizations and a “secular” state. It also considers how these conflicts escalated through the interaction of both structural and accidental factors, in particular: anti-Islamic discourses, social polarizations, and an accumulated potential for interethnic conflict in residential areas with a high number of migrants.<br
Keywords: Mosque conflicts; urban studies; Cultural; Social and Political Geography; Islam; Germany; Europe